Coordinated Satellite Observations of the Very Low Frequency Transmission Through the Ionospheric D Layer at Low Latitudes, Using Broadband Radio Emissions From Lightning. Issue 4 (6th April 2018) - Jacobson, Abram R.; Holzworth, Robert H.; Pfaff, Robert; Heelis, Roderick
Abstract: Both ray theory and full‐wave models of very low frequency transmission through the ionospheric D layer predict that the transmission is greatly suppressed near the geomagnetic equator. We use data from the low‐inclination Communication/Navigation Outage Forecast System satellite to test this semiquantitatively, for broadband very low frequency emissions from lightning. Approximate ground‐truthing of the incident wavefields in the Earth‐ionosphere waveguide is provided by the World Wide Lightning Location Network. Observations of the wavefields at the satellite are provided by the Vector Electric Field Instrument aboard the satellite. The data set comprises whistler observations with the satellite at magnetic latitudes <26°. Thus, our conclusions, too, must be limited to the near‐equatorial region and are not necessarily predictive of midlatitude whistler properties. We find that in most broadband recordings of radio waves at the satellite, very few of the lightning strokes result in a detectable radio pulse at the satellite. However, in a minority of the recordings, there is enhanced transmission of very low frequency lightning emissions through the D layer, at a level exceeding model predictions by at least an order of magnitude. We show that kilometric‐scale D ‐layer irregularities may be implicated in the enhanced transmission. This observation of sporadic enhancements at low magnetic latitude, made with broadband lightning emissions, is consistent with an earlier review of D ‐layer transmission for transmission from powerful man‐made radio beacons. Key Points: Lightning radio emissions are used to probe the ionospheric D layer's radio transmission at low latitudes The main tools in this study are the C/NOFS satellite and the World Wide Lightning Location Network We find sporadic enhanced transmission of VLF waves, well beyond the level predicted by laminar‐ionosphere models